Social Impact Bonds: a Review of their Strengths and Weaknesses. - Matos, Pedro Verga (2022)
This article analyses social impact bonds as an innovative instrument to finance projects in the social or environmental fields. These are instruments that require the collaboration of different stakeholders (multi-stakeholder approach), which may generate a new approach to social or environmental problems. When successful, they could save resources for States. They attract private capital to finance societal projects, allowing them, simultaneously, competitive remuneration and an effective impact. Since their remuneration/reimbursement is based on outcomes, there is a risk transfer (at least partially) from the public sector to the private sector. However, difficulties in articulation between the different participants and in the correct measurement of results/outcomes may limit the scope (size and timeframe) of the projects involved, as well as distract NGOs from their mission. Due to the growing importance of Social and Sustainable Finance in financial markets and public policies, the detailed study of these new instruments is highly recommended.